2012
DOI: 10.4103/0253-7613.91862
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-inflammatory effects of Broussonetia papyrifera stem bark

Wen-Tung Wu

Abstract: Objective:Broussonetia papyrifera is used as a traditional medicine to treat few diseases. However, the antiinflammatory effect of B. papyrifera stem bark has not been evaluated. The aim of this study is to investigate the effects of n-hexane fraction from methanol extract of B. papyrifera stem bark on lipopolysaccharide (LPS)-stimulated inflammation using RAW 264.7 cells.Materials and Methods:Methanol extract was obtained from B. papyrifera stem bark and its sequential fractions (hexane, dichloromathane, ethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…B. papyrifera extract is traditionally used for herbal medicine. In previous study results, B. papyrifera has demonstrated anti-inflammatory [16,17], antioxidant [18], antityrosinase [19], anticancer [20], antinociceptive [21], and antimicrobial effects [22]. Our study demonstrated that B. papyrifera extract treatment regulated WNT/β-catenin and IL-4 / STAT6 signaling pathways in hHFDP cells and stimulated hair growth in clinical subjects.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…B. papyrifera extract is traditionally used for herbal medicine. In previous study results, B. papyrifera has demonstrated anti-inflammatory [16,17], antioxidant [18], antityrosinase [19], anticancer [20], antinociceptive [21], and antimicrobial effects [22]. Our study demonstrated that B. papyrifera extract treatment regulated WNT/β-catenin and IL-4 / STAT6 signaling pathways in hHFDP cells and stimulated hair growth in clinical subjects.…”
Section: Introductionsupporting
confidence: 63%
“…In this study, we examined the potential of developing a hair growth promoting agent by using the extract of B. papyrifera, a medicinal plant belonging to the Moraceae family that is widely distributed in East Asia and China [18]. Previous studies have reported that B. papyrifera possesses anti-inflammatory, antioxidant, anti-tyrosinase, anticancer, antinociceptive, and antimicrobial properties [16][17][18]21,22]. Our study demonstrated that the native plant B. papyrifera is involved in cell cycle regulation of hair follicle cells, which are regulated via the activation of WNT-β-catenin and STAT6 signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological level of SCC in bulk cow milk is between 50×10 3 and 100×10 3 cells per mL, whereas 200×10 3 cells per mL is taken as the threshold to define a mammary quarter between healthy and infected [ 20 , 21 ]. In the present study, Group M and Group H had lower milk SCC than that of the control Group and Group L, which might due to the anti-inflammatory effect of the active ingredients in B. papyrifera [ 22 24 ]. It is reported that high content of milk protein was found in high SCC milk [ 25 ] and fat content was significantly increased from 3.55% to 3.72% by an increment of SCC from 100 to 200 cells/mL [ 26 ], but a decrease of milk protein content when SCC in milk was high [ 5 ].…”
Section: Discussionmentioning
confidence: 66%
“…The fruit extract is not only a traditional medicine for treating cardiovascular diseases, but also contains alkaloids as a drug candidate for treating cancer [35]. Stem bark has a high content of phenolic compounds and is a potential resource for medical pharmaceuticals and anti-inflammatory drugs [36,37]. The root system of the B. papyrifera is very developed.…”
Section: Introductionmentioning
confidence: 99%